Features on reshaping modern office resilient for time-crisis - Ng, Wei Bin (2023)
This study was carried out aim to understand what kind of a modern office that employees in Malaysia attract and willing to return physically after pandemic situation which by understanding the features of modern office that employees desired the most. However, there is a challenge which employees now in Malaysia are changed their working culture during the pandemic situation which work from home become a new normal of a workplace for them. This study has carried out to identify the office features design in the modern office and to analyse the modern offices features affected the employees to return in this post pandemic situation. This study has determined six major features of modern office that resilient timecrisis situation which included open plan layout design, ergonomic furniture, colour of office’s wall, relaxation and recreation areas in available space in office as well as lastly the lighting in the office. This study has carried out by collecting the questionnaire that feedback from the employee respondents. Then, all the data collected will be analysed by using Relative Importance Index (RII) which to rank which features are the most important based on the feedback from the employees. The result has stated that the most important of the features that should include in a modern office is office lighting. Appropriate lighting temperature in office area which has great impact on employees to work productivity and benefit health and wellbeing. It is important to know that employees now are not able to work as previously anymore before pandemic, thus, after the pandemic which few changes must be made to create new type of working experiences.